Pelatihan Publikasi Karya Ilmiah di Jurnal Nasional Bagi Guru SMP Negeri 2 Buay Madang Timur OKU Timur - Thoha Firdaus; Arini Rosa Sinensis; Widayanti Widayanti; Effendi Effendi (Jurnal Indonesia Mengabdi, 2022)
A community service has been carried out with the topic of Scientific Publication Training in the National Journal for Teachers of SMP Negeri 2 Buay Madang Timur which is embodied in an agenda with the theme of Publication Management. This service aims to provide training and understanding of scientific publications in the teacher's morning national journal. The method implemented is using training and mentoring methods regarding scientific publications in national journals. In the activity carried out several stages of material topics that lead to the main goal. The stages of the material presented include the importance of scientific publications to teachers, then continued with an explanation of what components are contained in scientific publications, and finally the practice of scientific publication training. After the activity took place the teacher felt helped by this training. Teachers become more aware of the importance of scientific publications for teachers, one of which is for functional promotions, teachers become more aware of how to make good and correct scientific papers, and teachers know and know how to publish scientific papers through the online submission process..